Contact to the out-of-hours service among Danish parents of small children – a qualitative interview study. (3rd April 2018) - Lass, Marie; Tatari, Camilla Rahr; Merrild, Camilla Hoffmann; Huibers, Linda; Maindal, Helle Terkildsen
Abstract: Objective: In Denmark, parents with small children have the highest contact frequency to out-of-hours (OOH) service, but reasons for OOH care use are sparsely investigated. The aim was to explore parental contact pattern to OOH services and to explore parents' experiences with managing their children's acute health problems. Design: A qualitative study was undertaken drawing on a phenomenological approach. We used semi-structured interviews, followed by an inductive content analysis. Nine parents with children below four years of age were recruited from a child day care centre in Aarhus, Denmark for interviews. Results: Navigation, information, parental worry and parental development appeared to have an impact on OOH services use. The parents found it easy to navigate in the health care system, but they often used the OOH service instead of their own general practitioner (GP) due to more compatible opening hours and insecurity about the urgency of symptoms. When worried about the severity, the parents sought information from e.g. the internet or the health care professionals. The first child caused more worries and insecurity due to less experience with childhood diseases and the contact frequency seemed to decrease with parental development. Conclusion: Parents' use of the OOH service is affected by their health literacy levels, e.g. level of information, how easy they find access to their GP, how trustworthy and authorized health information is, as well as how much they worry and their parental experience. These findings must be considered when planning effective health services for young families. Key points: The main findings are that the parents in our study found it easy to navigate in the healthcare system, but they used the OOH service instead of their own general practitioner, when this suited their needs. The parents sought information from e.g. the internet or the health care professionals when they were worried about the severity of their children's diseases. They sometimes navigated strategically in the healthcare system by e.g. using the OOH service for reassurance and when it was most convenient according to opening hours. The first child seemed to cause more worries and insecurity due to limited experience with childhood diseases, and parental development seems to decrease contact frequency. Overall, this study contributes with valuable insights into the understanding of parents' help seeking behaviour. There seems to be a potential for supporting especially first-time parents in their use of the out of hours services.